2017
DOI: 10.1038/s41467-017-00566-9
|View full text |Cite
|
Sign up to set email alerts
|

Fas cell surface death receptor controls hepatic lipid metabolism by regulating mitochondrial function

Abstract: Nonalcoholic fatty liver disease is one of the most prevalent metabolic disorders and it tightly associates with obesity, type 2 diabetes, and cardiovascular disease. Reduced mitochondrial lipid oxidation contributes to hepatic fatty acid accumulation. Here, we show that the Fas cell surface death receptor (Fas/CD95/Apo-1) regulates hepatic mitochondrial metabolism. Hepatic Fas overexpression in chow-fed mice compromises fatty acid oxidation, mitochondrial respiration, and the abundance of mitochondrial respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Leukemia, also known as blood cancer, is a kind of malignant tumor in the hematopoietic system. Generally, it can be divided into several types, such as acute lymphoblastic leukemia ( 46 ), acute myeloid leukemia (AML), and chronic myelocytic leukemia (CML) ( 47 ). Recent studies have demonstrated that the crude ethanolic extract of Marsdenia tenacissima (CME) exhibited strong cytotoxicity against CML cell lines K562 in vitro and in vivo , and this cytotoxicity was related to inducing cell cycle (G0/G1) arrest through upregulating cyclin D1 and cell apoptosis through upregulating pro-apoptosis proteins caspase-3, caspase-9 and Bax ( 3 ).…”
Section: Marsdenia Tenacissima Effects Against Hematologicalmentioning
confidence: 99%
“…Leukemia, also known as blood cancer, is a kind of malignant tumor in the hematopoietic system. Generally, it can be divided into several types, such as acute lymphoblastic leukemia ( 46 ), acute myeloid leukemia (AML), and chronic myelocytic leukemia (CML) ( 47 ). Recent studies have demonstrated that the crude ethanolic extract of Marsdenia tenacissima (CME) exhibited strong cytotoxicity against CML cell lines K562 in vitro and in vivo , and this cytotoxicity was related to inducing cell cycle (G0/G1) arrest through upregulating cyclin D1 and cell apoptosis through upregulating pro-apoptosis proteins caspase-3, caspase-9 and Bax ( 3 ).…”
Section: Marsdenia Tenacissima Effects Against Hematologicalmentioning
confidence: 99%
“…As the central metabolic site of lipogenesis (lipid synthesis) and fatty acid β-oxidation (lipid utilization), the liver is the dominant organ regulating the process of lipid metabolism, and disturbances in hepatic lipid metabolism, characterized as aberrant hepatic lipid accumulation, are closely linked to various metabolic and cardiovascular diseases, including metabolic syndrome, nonalcoholic fatty liver disease, atherosclerosis, and diabetes. 13,14 It is well known that hepatocytes are crucial cells involved in hepatic lipid metabolism. Fatty acids are synthesized in hepatocytes and then converted into triglycerides and finally exported into the blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (1996) revealed HBV may play a key role in the process of chronic hepatitis B by activating the expression of IGF1R, leading to liver fibrosis and progressing into HCC. FAS functions to modulate hepatic mitochondrial metabolism and fatty acid oxidation contributing to nonalcoholic fatty liver disease, which generally develops to liver fibrosis and HCC (Cullen and Martin, 2015;Item et al, 2017). This study explains the activation of potential carcinogenic signals by immune factor receptors (Pitt et al, 2016).…”
Section: Discussionmentioning
confidence: 78%